The brain drain of teachers in South Africa: identifying the dynamics of its push factors - Mlambo, Victor. H.; Adetiba, Toyin. C. (Penerbit Universiti Kebangsaan Malaysia, 2020)
South Africa over the years has been losing a considerable number of teachers and this has become a growing concern among policymakers. Therefore, the objective of this paper is to identify the factors that are responsible for enticing teachers to migration out of South Africa. Using a strict textual analysis of the relevant literature, this paper reveals that South Africa has failed to reduce the emigration of teachers due to poor salaries and working conditions, subsequently, this has seen as agents from developed countries (recently Asian countries) aggressively recruiting teachers from the country. Other factors include poor infrastructure and limited career progression opportunities. The study showed that the brain drain of teachers results in a shortage of teachers in rural areas and increased inefficiency in the public educational system. It is therefore suggested that the government should make the retention of teachers a priority through incentives such as promotion, better salaries and the upgrading of infrastructure. The study concluded that teacher emigration has been a long-existing issue in South Africa and the mere fact that there has been no clear cut plan on how to deal with it is deeply worrying, moreover, today in South African schools, the issue of security has become a focal point, the failure to guarantee the safety of teachers in schools has been seen as a new factor encouraging migration either within the country or abroad.